Numerical analysis for engineers methods and applications - Ayyub, Bilal M.; McCuen, Richard H. 1941- (Textbooks in mathematics, 2016)
Emphasizing the practical aspects of their use, this text introduces numerical methods. It establishes their limitations, advantages and disadvantages, and is intended to assist future as well as practicing engineers in understanding the fundamentals of numerical methods.